How Do Depositors Respond to Bank Dividend Policy? Evidence from Market Discipline, Global Financial Crisis and COVID-19 Pandemic - Tran, Dung Viet (Asian Academy of Management Journal of Accounting and Finance, 2022)
Our study investigates how depositors respond to the bank dividend policy via the interest rate channel. The results suggests that by paying dividend, banks mitigate the information asymmetry between insiders and outsiders, then enjoying a lower deposit cost than banks that do not pay dividend. Dividend-paying banks that are subject to higher funding costs may enjoy a greater decrease of funding costs than non-payers. Banks that are under greater pressure from regulators, but encounter losses have to pay higher deposit costs when deciding to pay dividend. The study emphasizes the downside of deposit insurance scheme when documenting the indifference of insured but uninsured depositors during the global financial crisis, but the COVID-19 crisis, suggesting the wake-up calls for depositors.